MARCO ANTONIO DE DOMINIS (GOSPODENTIĆ) - ROMAN CATHOLIC THEOLOGIAN, SCHOLAR AND ECUMENICAL - Fajfrić, Boris Ž. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Marco Antonio de Dominis (Gospodentić) was the archbishop, who was regarded as a great theologian and scientist. He preached the gospel of Christ, not the newness of Pope and his associates. He was not afraid to publicly criticize Rome and his works, which is why he was forced to leave his country and temporarily settled in England. Publicly advocated the unity of all churches, regardless of their differences, and the Church of Rome attributed the main blame for the split. That is why the Inquisition declared a heretic and condemned him posthumously.